2013
DOI: 10.1038/tpj.2013.33
|View full text |Cite
|
Sign up to set email alerts
|

The potential impact of pharmacogenetic testing on medication adherence

Abstract: Poor medication adherence is a well-known problem, particularly in patients with chronic conditions, and is associated with significant morbidity, mortality, and health care costs. Multi-faceted and personalized interventions have shown the greatest success. Pharmacogenetic (PGx) testing may serve as another tool to boost patients’ confidence in the safety and efficacy of prescribed medications. Here we consider the potential impact (positively or negatively) of PGx testing on medication-taking behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…Thus, analysis of particular genetic variants through PGx testing may help optimize pharmaceutical therapy by identifying patients with these polymorphisms and better informing the selection of the proper drug and dosage and reducing risk of ADRs. The substantial healthcare costs associated with ADRs [58], the increasing use of prescription drugs in the USA [9] and other potential benefits of PGx testing such as increased medication adherence [10,11] provide further support for the use of PGx testing to personalize care.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, analysis of particular genetic variants through PGx testing may help optimize pharmaceutical therapy by identifying patients with these polymorphisms and better informing the selection of the proper drug and dosage and reducing risk of ADRs. The substantial healthcare costs associated with ADRs [58], the increasing use of prescription drugs in the USA [9] and other potential benefits of PGx testing such as increased medication adherence [10,11] provide further support for the use of PGx testing to personalize care.…”
Section: Introductionmentioning
confidence: 99%
“…It becomes part of their personal medical history to be shared with healthcare professionals. If the use of a patient's pharmacogenetic information improves their chance of a good clinical response, or reduces their side effects and improves tolerability, then the patient is more likely to take their medication, with compliance being crucial to positive treatment outcomes [11]. It seems inevitable that pharmacogenetics and its core role in personalized medicine will become the standard of care in the future.…”
Section: Editorialmentioning
confidence: 99%
“…A study has shown that pharmacogenetic testing may serve as another tool to boost patients' confi dence in the safety and effi cacy of prescribed medications (Haga and LaPointe 2013 ). It has a positive impact on medication-taking behavior and reduces non-compliance which is well-known in patients with chronic conditions, and is associated with signifi cant morbidity, mortality and health-care costs.…”
Section: Role Of Patientsmentioning
confidence: 99%